2022
DOI: 10.1002/jcla.24396
|View full text |Cite
|
Sign up to set email alerts
|

Silencing oncogene cell division cycle associated 5 induces apoptosis and G1 phase arrest of non‐small cell lung cancer cells via p53‐p21 signaling pathway

Abstract: Backgrounds: As a regulator of cell cycle, cell division cycle-associated 5 (CDCA5) is involved in the progression of various malignant tumors. However, the potential relationship between CDCA5 and lung cancer has not been reported. Methods:In our study, we analyzed the expression of CDCA5 in a variety of malignant tumors, performed Kaplan-Meier survival analysis of lung adenocarcinoma (LUAD), explored the potential relationship between CDCA5 expression and clinicopathological characteristics, assessed the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…This study indicated that CDCA5 expression could impact TMB, MSI and immune cell infiltration and thus impacting response to immunotherapy for the first time. Besides, positive relationship of CD274 (PD-L1) and CDCA5 was found in most tumors, which was in line with the finding of Shen et al 13 Therefore, there is potential for CDCA5 to serve as a new immunotherapeutic target. However, the potential mechanisms should be identified through in vitro and in vivo experiments.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This study indicated that CDCA5 expression could impact TMB, MSI and immune cell infiltration and thus impacting response to immunotherapy for the first time. Besides, positive relationship of CD274 (PD-L1) and CDCA5 was found in most tumors, which was in line with the finding of Shen et al 13 Therefore, there is potential for CDCA5 to serve as a new immunotherapeutic target. However, the potential mechanisms should be identified through in vitro and in vivo experiments.…”
supporting
confidence: 87%
“…12 A recent study demonstrated the positive relationship between CDCA5 and PD-1/PD-L1 in non-small-cell lung cancer (NSCLC). 13 However, there is still no systematic analysis on the relationship of CDCA5 in different human cancers based on large clinical data.…”
Section: Introductionmentioning
confidence: 99%
“…We performed DO/GO/KEGG functional enrichment analysis on these core genes and found that these genes were strongly associated with the progression of NSCLC. In particular, KEGG analysis results showed that these core genes were enriched in pathways such as platinum resistance [43], Cellular senescence [44] and P53 signaling pathway [45], This also suggests that the hub gene may affect NSCLC through those ways.…”
Section: Discussionmentioning
confidence: 94%
“…CDCA5 can also promote cell proliferation and participate in apoptosis by regulating the function of cell cycle related proteins and transcription factors [10]. As reported, upregulated CDCA5 expression level was found in many types of cancers, including bladder cancer, lung cancer, liver cancer, colorectal cancer, indicating CDCA5 may participate in the development of these diseases [11][12][13][14]. However, the functional role of CDCA5 in ccRCC progression remains unclear.…”
Section: Introductionmentioning
confidence: 86%